DETEKSI KECURANGAN LAPORAN KEUANGAN DENGAN DIAMOND FRAUD THEORY PADA PERUSAHAAN SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Walid Rudianti; Siti Maesaroh (STIE Pelita Nusantara Semarang, 2022)
The characteristics of the quality of financial reports are that financial statements must be reliable, the reliability of information in financial statements is influenced by several factors, namely honest presentation, substance over form, neutrality, sound judgment, completeness. However, there are still companies that commit fraud in financial statements. Fraud is an unlawful act that contains elements of intent, malicious intent, fraud, concealment and abuse of trust, with the aim of taking illicit profits which can be in the form of money, goods/wealth, and others. Fraud financial statements can be detected using the Diamond Fraud Theory. This study aims to determine the factors that influence financial statement fraud. The population of this study are transportation companies listed on the Indonesia Stock Exchange in 2015 – 2018. The number of companies listed is 27 companies, after sampling using purposive sampling where only companies that earn profits are included in the research sample. From the entire population, a sample of 8 companies was obtained, with observations for 4 years, data were obtained from 32 companies' financial statements. The results of this study state that partially pressure, opportunity and rationalization have no effect on financial statement fraud, while the capability variable has an influence on financial statement fraud. The results simultaneously state that pressure, opportunity, rationalization and capability affect financial statement fraud.